The Production of the Black Body in American Necropolitics - Văetiși , Șerban (AMERICANA E-journal of American Studies in Hungary, 2021)
Thought as a critical interpretive essay of George Floyd’s death under police custody in 2020, the article further explores the conditions, factors and practices of racism in American society and politics. Emphasizing the centrality of the black body as social-cultural construction and the relevance of such materialist concepts as blackness, embodiment and bare life, the analysis focuses on the concept of “production” in interpreting the biopolitical/necropolitical relations created among and through categories of race in America, and more generally and theoretically, in history and society. The article provides a rereading of racism through the lecture of Achille Mbembe’s Critique of Black Reason and some others of his contributions, including the seminal Necropolitics article and the more recent Brutalisme. The major contribution brought by this essay is the suggestion of an analytical model of interpreting racism through critically reconceptualizing the Marxian notion of “mode of production” in the production of the black body in a given socio-political context, fueled by specific historical and cultural practices.